Design a novel inhibitor for corrosion protection in oil and gas environments - Suziella, Awang (2013)
This is a study on the designing and performance of corrosion inhibitor in oil and gas environments. The objective of this project is to determine the right composition of a corrosion inhibitor that can be used as corrosion protection in oil and gas environments. A suitable parameter to imitate the oil and gas environment used as guideline in this project which is a solution of 30% NaCl, room temperature, carbon steel as the experiment specimen. The data analyzed by using LPR (Linear Polarization Resistance) to determine the corrosion rate. the composition selected for the corrosion inhibitor is palm oil and amine. The minimum corrosion rate obtained from the experiment is 1.345 mmPY which is the combination of 2.0 ml palm oil and 3.0 ml of amine. Finally, by considering the result of each experiment that had been conducted, the composition of palm oil and amine can be used as a corrosion inhibitor.